Effect of cytochalasin-B on TIO2 nanoparticles uptake by different cell lines - Brandão, Fátima (2019)
The in vitro cytokinesis-block micronucleus cytome assay (CBMN) is widely used for genotoxicity evaluation of nanomaterials (NMs). However, cytochalasin-B (Cyt-B) used in this test may affect the uptake of NMs due to possible interference with endocytosis. Thus, the aim of this study was to investigate the influence of Cyt-B on the uptake of TiO2 nanoparticles (TiO2 NPs) by four different human cell lines: lung cells (A549), glial cells (A172), neurons (SH-SY5Y), and liver cells (HepG2).